Pengaruh Penggunaan Model Quantum Teaching Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Di Kelas V SDN 07 Sitiung Kabupaten Dharmasraya - Misriyana; Fitria Sari; Alchonity Harika Fitria (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2022)
The use of learning models that are not appropriate during the learning process causes students to be bored and bored so that students are less active during learning activities so that students do not understand the material because there is too much material and mostly take notes, and the impact on learning outcomes is very low. The Quantum Teaching model of this researcher aims to determine the effect of the Quantum Teaching model to show the results of the process of occurrence of an event according to the teaching material. This type of research is a pre-experimental research design in the form of One Group Pretest-Posttest Design (initial test-single group final test). The population in this study were all students in class V SDN 07 Sitiung, Dharmasraya Regency who were registered in the 2020/2021 academic year. The technical analysis of data collection in this study was through normality testing and hypothesis testing through SPSS 22 at a significant level of 0.05. The results showed that the Quantum Teaching model can improve student learning outcomes, it can be seen from the average pretest and posttest obtained from fifth grade students at SDN 07 Sitiung by obtaining an average pretest of 67.33 and posttest 78.76. Based on the analysis conducted, the significance value = 0.000 < 0.05. Thus, there is a positive and significant effect between the Quantum Teaching model on social studies learning outcomes for fifth grade students at SDN 07 Sitiung, Dharmasraya Regency